Effect of Mepiquat Chloride on Phenology, Yield and Quality of Cotton as a Function of Application Time Using Different Sowing Techniques - Khadija Murtza; Muhammad Ishfaq; Nadeem Akbar; Saddam Hussain; Shakeel Ahmad Anjum; Najat A. Bukhari; Amal Mohamed AlGarawi; Ashraf Atef Hatamleh (Agronomy, 2022)
Mepiquat chloride (MC) is a plant growth regulator used to manage the rampant vegetative growth of cotton. A two-year field experiment was conducted at the Postgraduate Agricultural Research Station, University of Agriculture, Faisalabad, Pakistan, during 2017 and 2018 to investigate the influence of MC applied at different times on phenology, morphology, lint yield and quality of cotton cultivated using different sowing techniques. MC was applied 50 days after sowing (DAS), 60 DAS and 70 DAS to cotton planted in flat fields (flat sowing), ridges (ridge sowing) and beds (bed sowing). The interactive effect of MC application time and sowing technique did not influence crop phenology, morphology, and lint yield and quality. It was revealed that the crop planted on beds took fewer days to flower (10%) as compared to that on the flat field, and the bed-sown crop produced a higher number of opened bolls (60%) and was characterized by a higher boll weight (32%) and seed cotton yield (50%) in comparison to the flat-sown crop. A late application of MC (at 70 DAS) caused a significant reduction in the time to flowering (8%), with a simultaneous increase in the number of opened bolls (60%), boll weight (32%), ginning out turn (8%) and lint yield (27%) as compared to MC application at 50 DAS. In terms of lint quality, cotton planted on beds had better fiber uniformity (8%) compared to that on the flat field, while MC applied at 70 DAS produced better fiber fineness by 27% in comparison to MC applied earlier. Overall, cotton planting on beds and MC application at 70 DAS may help improve cotton yield and fiber quality and may help in the mechanical picking of cotton.